High-time-resolution analysis of meridional tides in the upper mesosphere and lower thermosphere at mid-latitudes measured by the Falkland Islands SuperDARN radar - G. Chisham; A. J. Kavanagh; N. Cobbett; P. Breen; T. Barnes (Annales Geophysicae, 2024)
Solar tides play a major role in the dynamics of the upper mesosphere and lower thermosphere (MLT). Hence, a comprehensive understanding of these tides is important for successful modelling of the MLT region. Most ground-based observations of tidal variations in the MLT have been from meteor radar measurements with a temporal resolution of 1 h. Here, we take a different perspective on these tidal variations using high-resolution 1 min neutral-wind measurements from the Falkland Islands SuperDARN (Super Dual Auroral Radar Network) radar. This analysis shows that these higher-resolution data can be used to identify higher frequency tidal components than are typically observed by meteor radars (up to a heptadiurnal component). It also shows evidence of significant power in these higher frequency components, particularly in the quaddiurnal component, which may be particularly suitable for a global analysis using high-resolution SuperDARN neutral-wind measurements. The high-resolution analysis also shows evidence of fluctuations with a frequency of 1.5 cycles per day, as well as higher-frequency fluctuations, accompanying a quasi-2 d (two day) wave. We discuss the limitations of this high-resolution analysis method and the new opportunities that it may provide. We conclude that higher-resolution SuperDARN neutral-wind measurements need to be better exploited in the future as they provide a complementary way of studying tides and waves in the MLT.